Barriers to participation in religious adult education: an exploratory study - Selman, John Thomas Jr (Kansas State University, 2013)
Millions of Americans profess belief in God and follow a Protestant Christian belief system. However, very little research or literature explores their participation in religious adult education. Several areas within adult education are exhaustively researched such as health care, leisure, and career related courses, but studies within religion go largely unexamined. This study sought to develop an understanding concerning deterrents to participation in religious adult education. Additionally, this study sought to compare deterrents in the Protestant Christian church to deterrents experienced by the general adult population in their pursuit of education. This study used a modified Deterrents to Participation Scale-General (DPS-G) Likert scale survey to gather both demographic and barrier to participation information. Data collected from the survey was analyzed using a variety of descriptive and nonparametric statistical tests. Comparative analyses were conducted to liken deterrents to participation in religious adult education to the general adult population. The study revealed that all six deterrents to participation categories found on the DPS-G survey instrument had a bearing on a Protestant Christian’s religious adult education participation. The barrier to participation found to deter the most demographic groups was personal problems. This deterrent was followed in order of magnitude by: lack of confidence, time, lack of relevance, low personal priority, and cost. This study also found that barriers deterring adult Protestant Christian participation vary from those deterring the general adult population’s participation in secular educational programs. This study was exploratory and, as such, can be used for future researchers to examine why certain deterrents impact certain demographic groups. However, in the interim this research can be used for religious adult education program planners to better understand deterrents to participation and develop courses of action to help overcome these barriers.
Keywords: Adult education; Religion; Adult Education (0516)